GROWTH PRODUCTIVITY OF BROILER CHICKEN THROUGH DRINKING WATER - I N. D., Darma; Mudita, I M.; Sutama, I N. S. (Jurnal Peternakan Tropika; Vol 11 No 2 (2023): Vol. 11 No. 2 Tahun 2023; May - August, 2023)
This study aims to determine the productivity of broilers given the probiotic “Probio-Bali Tani which has been carried out in Penglipuran Village, Bangli Regency, Bali Province for 1.5 months. This study used a completely randomized design (CRD) consisting of 2 treatments and 10 replications. A = Broilers who were not given "Probio-BaliTani" probiotics through drinking water (regular drinking water in the form of PDAM water), B = Broilers who were given "Probio-BaliTani" probiotics as much as 0.02% of the target body weight/week. The variables observed included weight gain, feed consumption, FCR, initial and final body weight, mortality, harvest age and performance index (IP). The results of this study indicate that weight gain, final body weight and Performance Index (IP) get results that treatment B is higher, respectively, by 10.8884%, and 9.3099%, 19.3939 compared to treatment A, while consumption and The FCR of treatment B was 1.1768% and 9.591% lower than treatment A. At the harvest age of this study was the same, namely 42 days, while the initial weight of treatment A was 5.4876% lower than treatment B. Based on the above research, it can be concluded that the administration of probiotics "Probio-Bali Tani" of 0.02% in drinking water was able to increase body weight growth, feed consumption and was able to significantly reduce FCR and also increase the performance index but not significantly. Keywords: Probiotics “Probio-Bali Tani, Broiler Chicken, Productivity